Induced Preferences - Welfare Economics - Freedom - Christian von Weizsäcker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Is welfare economics still possible, when preferences are endogenously determined? The answer is yes, if and only if the hypothesis of adaptive preferences is correct. If preferences satisfy the conditions of continuity, non-satiation and regularity, then adaptive preferences imply that improvement sequences are non-circular (acyclic): Theorem 1. And non-circularity of improvement sequences implies that there exists an exogenous quasi-utility function V(x), such that V(y)>V(x) indicates that y can be reached from x via an improvement sequence: Theorem 2. As a corollary preferences then are adaptive. I define pragmatic compossibility of rights as a condition for a free society. Their specific form can only be obtained by experience, i.e. piecemeal engineering la Karl Popper. For this concept of the Open Society to be feasible preferences have to be adaptive. Partial equilibrium cost-benefit analysis remains valid if and only if preferences are adaptive: Theorem 3. This is a requirement for a society which can escape stagnation by means of the money form of decentralised decision making. The success of western society through the last several centuries is proof that preferences are adaptive.
Keywords: D01; D61; K10; 330